KAJIAN PERCEPATAN PROYEK MENGGUNAKAN METODE TIME COST TRADE OFF DENGAN SYSTEM PENAMBAHAN PEKERJA (STUDI KASUS : PEMBANGUNAN GEDUNG RS JANTUNG PARAMARTA BANDUNG) - Syapril Janizar; Taufiq Rahman; Lucky Amperawan Schipper (Departement of Civil Engineering, Universitas Winaya Mukti, 2023)
This The background of this research is based on the implementation of building construction where there is often a discrepancy between the planned schedule and the realization in the field which can result in an increase in implementation time and an increase in implementation costs so that project completion is hampered. In this case requires implementation management in accordance with the current situation and conditions. There are several methods that can be used to prevent delays in the implementation of development, one of which is the Time Cost Trade Off method or also known as the cost-to-time exchange method. Time Cost Trade Off is a method used to speed up project implementation time by testing all activities in a project. The construction of the Paramarta Heart Hospital is on Jalan Soekarno Hatta No. 581 London. The project is handled by PT. GIAN GHEANA GAVIN ABADI. The purpose of this research is to find out how much the time cost trade off method reduces after the Time Cost Trade Off method is applied and to find out how much cost is needed after the time cost trade off method is applied. Based on the results of the analysis of the completion of the Hospital Building Construction Project. The heart of Paramarta before acceleration takes 273 days, but after acceleration it takes 220 days. The cost required before acceleration is Rp. 33,604,992,000.00, but after acceleration, a fee of Rp. 29,440,707,778.00.